Paediatric unplanned reattendance rate: A&E clinical quality indicators. Issue 3 (2nd January 2013) - O'Loughlin, Kate; Hacking, Katie A; Simmons, Naomi; Christian, William; Syahanee, R; Shamekh, Ahmed; Prince, Nicholas J
Abstract : The new accident and emergency (A&E) unplanned reattendance rate clinical quality indicator is intended to drive reduction of avoidable reattendances. Validation data for reattendance rates in children are awaited. The aim of this three site observational study is to establish the rate and reasons for unplanned reattendance to UK paediatric A&Es. Each centre undertook retrospective case note review of children attending at least twice within 7 days. Unplanned reattendance rates at the three centres were 5.1%, 5.2% and 4.4%. Reducing unnecessary unplanned reattendances is beneficial for patients, service capacity and efficacy. This study has identified two groups for targeting reattendance reduction: parents of children returning with the same diagnosis, severity unchanged and parents who bypass primary care resources. Clear communication and early involvement of experienced clinicians are paramount. This study has indicated that a 1%–5% unplanned reattendance rate is realistic, achievable and can drive improvement in children's services.